Brahmi rasayana Improves Learning and Memory in Mice. Issue 1 (2006) - Joshi, Hanumanthachar; Parle, Milind
Abstract : Cure of cognitive disorders such as amnesia, attention deficit and Alzheimer's disease is still a nightmare in the field of medicine. Nootropic agents such as piracetam, aniracetam and choline esterase inhibitors like Donepezil® are being used to improve memory, mood and behavior, but the resulting side effects associated with these agents have made their use limited. The present study was undertaken to assess the potential of Brahmi rasayana (BR) as a memory enhancer. BR (100 and 200 mg kg−1 p.o.) was administered for eight successive days to both young and aged mice. Elevated plus maze and passive-avoidance paradigm were employed to evaluate learning and memory parameters. Scopolamine (0.4 mg kg−1 i.p.) was used to induce amnesia in mice. The effect of BR on whole brain AChE activity was also assessed. Piracetam (200 mg kg−1 i.p.) was used as a standard nootropic agent. BR significantly improved learning and memory in young mice and reversed the amnesia induced by both scopolamine (0.4 mg kg−1 i.p.) and natural aging. BR significantly decreased whole brain acetyl cholinesterase activity. BR might prove to be a useful memory restorative agent in the treatment of dementia seen in elderly.